2022
DOI: 10.1177/19458924221135709
|View full text |Cite
|
Sign up to set email alerts
|

Fashioned Mucoperichondrial Flap Technique Versus Fishing Line Technique in the Repair of Septal Dislocation: A Prospective Comparative Study

Abstract: Background A nasal septal dislocation is a common form of septal deviation with many challenges and different surgical techniques for correction. Objective To assess the efficacy of fashioned mucoperichondrial flap technique versus fishing line technique in the repair of septal dislocation. Methods The study was a prospective comparative cohort study conducted on 88 patients aged above 18 years who have symptomatic mild to moderate caudal septal dislocation spanning the period from June 2021 to June 2022. Preo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…They found that application of hyaluronic acid significantly enhanced the success rate and reduced scaring and granulation after surgery. Along similar lines, several studies compared outcomes after different surgical techniques: Abo El Naga and Hamdan 14 prospectively evaluated two surgical techniques for repairing septal dislocations and Zhang et al 15 performed a systematic literature review comparing multiple techniques to treat inferior turbinate hypertrophy.…”
mentioning
confidence: 99%
“…They found that application of hyaluronic acid significantly enhanced the success rate and reduced scaring and granulation after surgery. Along similar lines, several studies compared outcomes after different surgical techniques: Abo El Naga and Hamdan 14 prospectively evaluated two surgical techniques for repairing septal dislocations and Zhang et al 15 performed a systematic literature review comparing multiple techniques to treat inferior turbinate hypertrophy.…”
mentioning
confidence: 99%